PENGHAMBATAN PELEPASAN ENZIM -HEXOAMINIDASE DARI SEL MAST OLEH ZEORIN, SENYAWA DARI AEGLA MARMELOS CORREA - Agung Endro Nugroho; Sugeng Riyanto; Mohd. Aspollah Hj. Sukari; Kazutaka Maeyama (Jurnal Ilmiah Farmasi, 2007)
ABSTRACTZeorin or 6,22-Dihydroxyhopane is a compound isolated from Aegle marmelos Correacollected in Yogyakarta Indonesia. The molecular structure was confirmed in Universiti PutraMalaysia. This compound was obtained from petroleum ether extract of the leaves of Aeglemarmelos Correa. In present study, we investigated the effects of zeorin on the -hexoaminidaseenzyme release from mast cell culture. The experiment was performed by using rat basophilicleukemia (RBL-2H3) cell line, a tumor analog of mast cells. DNP24-BSA and thapsigargin were usedas immunologic and non-immunologic inducers for -hexoaminidase enzyme release from mastcells, respectively. The release of -hexoaminidase enzyme was determined by using colorimetricmethods with an enzyme substrate, p-nitrofenil-2-Acetamido-2-deoksi--D-gluko-piranosida, and amicroplate reader at 405 nm. In this study, treatment of 20 ng/mL DNP24-BSA and 0.5 Mthapsigargin could stimulate the release of -hexoaminidase enzyme from RBL-2H3 cells by25.421.62 % and 33.163.72 %, respectively. Zeorin showed potent inhibitory effects on the -hexoaminidase enzyme release, when the release induced by DNP24-BSA. In contrast, zeorin showweak inhibitory effects, when the -hexoaminidase enzyme release from RBL-2H3 cells induced bya Ca2+stimulant, thapsigargin. The IC50 values of zeorin’s effects on DNP24-BSA and thapsigarginexperiments were 33,71 M and >100 M, respectively. Based on the results, the inhibitory effect ofzeorin on the -hexoaminidase enzyme release from RBL-2H3 cells involving mechanisms relatedto the interaction of IgE on the mast cell surface or intracellular signal transductions involved inmast cell degranulation.Key words : Aegle marmelos Correa, zeorin, sel mast, -hexoaminidase enzyme